Networked mobile robot leader-follower trajectory tracking control with delays. (2018) - Feng, Jian; Qiu, Xiang; Zhang, Wen-An
We consider the leader-follower trajectory tracking control problem for networked mobile robots. The leader and follower communicate with each via communication network and the network-induced delays are considered. Firstly, an uncertain system model is presented to describe the leader-follower trajectory tracking control system with delays, where the dynamics induced by the uncertain part of the delay is described by the model uncertainties. Secondly, an extended state observer (ESO) is designed to estimate the uncertainty of the trajectory tracking control system, and then the uncertainties induced by the delays are compensated by the ESO using dynamic linearisation compensation. In this way, the effects of the network induced delays are removed and the linear active disturbance rejection control (LADRC) method is thus implemented to achieve the objective of high performance trajectory tracking control. Finally, an illustrative example is presented to show the effectiveness and superiority of the proposed method.